Integrated Multiomics Analyses Revealing Different Molecular Profiles Between Early- and Late-Stage Lung Adenocarcinoma - Yue, Dongsheng; Liu, Weiran; Gao, Liuwei; Zhang, Lianmin; Wang, Tao; Xiao, Shanshan; Fu, Yingxue; Li, Nan; Lin, Rui; Hu, Yao; Ding, Lieming; Zhang, Zhenfa; et al. (Frontiers in Oncology, 2021)
The molecular differences in genetic and epigenetic profiling between early-stage (ES) and late-stage (LS) lung adenocarcinoma (LUAD), which might help to understand cancer progression and biomarker guided precision treatment, need further be investigated. In this study, we performed comprehensive analysis using multi-omics next-generation sequencing (NGS) on tissue samples from 7 ES (stage I) and 10 LS (stage III/IV) LUAD patients to study molecular characteristics between the two groups. Characterization of the genomic and transcriptomic profiles showed stage-specific somatic mutations, copy number variations (CNVs) and differentially expressed genes (DEGs). LS samples tend to have more TP53, ERBB2 and CHD4 mutations. Gene copy number loss occurs in immune-related gene pathways in the late stage of LUAD. ATAC-seq analysis showed that LS samples harbored more open chromatin peaks around promoter regions and transcription start sites (TSS) than ES samples. We then identified the known transcription factor (TF) binding motifs for the differentially abundant ATAC-seq peaks between the ES and LS samples and found distinct regulatory mechanisms related to each stage. Furthermore, integrative analysis of ATAC-seq with WGS and RNA-seq data showed that the degree of chromatin accessibility is related to copy number changes, and the open chromatin regions could directly regulate the expression of some DEGs. In conclusion, we performed a comprehensive multi-omics analysis of the early and late stages of LUAD and highlighted some important molecular differences in regulatory mechanisms during cancer progression. Those findings help to further understand mechanism and biomarker related targeted therapy.